2012
DOI: 10.1097/jom.0b013e3182636e93
|View full text |Cite
|
Sign up to set email alerts
|

Serum Heme Oxygenase-1 as a Marker of Lung Function Decline in Patients With Chronic Silicosis

Abstract: Serum HO-1 may be a predictor of lung function decline in silicosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…The protective properties of HO-1 are multifactorial and likely due to degradation of pro-oxidant heme, the generation of antioxidant biliverdin and bilirubin, and the production of carbon monoxide, which is a potent vasodilator with anti-inflammatory effects (7,9). Furthermore, previous studies have also observed reduced serum HO-1 in lung disease (31). The presence of HO-1 has recently been demonstrated in various intracellular and extracellular compartments, suggesting that this protein may exhibit other functions independently of its known enzymatic activity (18,20,32).…”
Section: Discussionmentioning
confidence: 99%
“…The protective properties of HO-1 are multifactorial and likely due to degradation of pro-oxidant heme, the generation of antioxidant biliverdin and bilirubin, and the production of carbon monoxide, which is a potent vasodilator with anti-inflammatory effects (7,9). Furthermore, previous studies have also observed reduced serum HO-1 in lung disease (31). The presence of HO-1 has recently been demonstrated in various intracellular and extracellular compartments, suggesting that this protein may exhibit other functions independently of its known enzymatic activity (18,20,32).…”
Section: Discussionmentioning
confidence: 99%
“… 32 34 Of interest, these findings suggest that serum HO-1 levels might be markers of disease severity in individuals exposed to silica. 35 …”
Section: Therapy Of Silicosismentioning
confidence: 99%
“…In the present study, we measured the lung function of individuals to investigate the possible relationship between lung function loss and silicosis. We focus on FEV 1 and FVC, which were usually used to evaluate lung function loss in silicosis [35][36][37][38]. We found that FVC% pre, FEV 1 % pre, and FEV 1 /FVC (%) were decreased in the silicosis group.…”
Section: Discussionmentioning
confidence: 96%